PENERAPAN PEMBELAJARAN MATEMATIKA REALISTIK INDONESIA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VB SD NEGERI 86 PEKANBARU - Labamba, Nuri Andre; Marhadi, Hendri; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the low value of math. Preliminary data result of learning students of class VB SD Negeri 86 Pekanbaru is from the 23 students, only 10 peoples or 43,47% completed or reached the KKM and 13 peoples or 56,52% were not completed. Based on these problems, it is necessary given way to solve the problem include applying of Realistic Math Learning Indonesia. Realistic Math Learning Indonesia show the students the truth story and example from the real life of the lesson, then the students can understand the lesson well. Data collection instrument on this research are observation sheet activities of teacher and student, and learning outcomes. Subjects in this research were students of class VB of 86 elementary school Pekanbaru. This research was conducted in two cycles, by doing the daily test of the end of each cycle. The result of this research shows that Realistic Math Learning Indonesia can increase math studies, completeness math learning outcomes in first cycle is 65,21%, in second cycle increased to 86,96%.Keywords: Learning Math Realistic Indonesia, Mathematics Learning Outcomes.